Rancang Bangun Aplikasi Pelacak Bibit Kelapa Sawit Berbasis Aplikasi Mobile - Lukmannil Hakim; Feri Candra (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
The success of oil palm cultivation is deeply depend by quality of the seedlings, and for this reason the implementation of nurseries needs a special attention. The problem that occurs regularly is that the amount of seeds sent from the nursery area is not equal to the amount of seeds contained in the farm. The number of seeds that are not allocated causes misfortunes in the organization. Seedlings are also defenseless and can be replaced by different seeds on their way. An application is required and you can work with a lot of data. This application is expected to have the option to record status of the palm oil seedling area productively. Ionic is a system that can create hybrid mobile applications. This versatile application is built with commonly used programming language for the web (HTML, CSS, and JavaScript). This application will be used in places with network problems. Documenting changes in seed information status provides types of seed information assistance to the Board. This application works with both online and offline databases. Keywords: Palm oil, nursery, mobile hybrid application, data management